Plyometrics Can Preserve Peak Power During 2 Months of Physical Inactivity: An RCT Including a One-Year Follow-Up - Kramer, Andreas; Kümmel, Jakob; Gollhofer, Albert; Armbrecht, Gabriele; Ritzmann, Ramona; Belavy, Daniel; Felsenberg, Dieter; Gruber, Markus (Frontiers in Physiology, 2018)
Objective: Inactivity results in a marked loss of muscle function, especially in movements requiring high power, force and rate of force development. The aim of the present study was to evaluate if jump training can prevent these deteriorating effects of physical inactivity. Methods: Performance and muscle activity during several types of jumps was assessed directly before and after 60 days of bed rest as well as during follow-up visits in 23 male participants. Participants in the jump training group (JUMP, 12 participants) trained 5-6x per week during the bed rest period in a sledge jump system that allows jumps in a horizontal position, whereas the control group (CTRL, 11 participants) did not train. Results: Performance and muscle activity considerably decreased after bed rest in the control group but not in the training group, neither for countermovement jumps (peak power CTRL -31%, JUMP +0%, group x time interaction effect p<0.001), nor for squat jumps (peak power CTRL -35%, JUMP +1%, p<0.001) and repetitive hops (peak force CTRL -35%, JUMP -2%, p<0.001; rate of force development CTRL -53%, JUMP +4%, p<0.001). The control group’s performance had returned to baseline three months after bed rest. Conclusion: Despite the short exercise duration, the jump training successfully prevented power and strength losses throughout two months of bed rest. Thus, plyometrics can be recommended as an effective and efficient type of exercise for sedentary populations, preventing the deterioration of neuromuscular performance during physical inactivity.